BREEDING ZONES BASED ON GENOTYPE-ENVIRONMENT INTERACTION IN SEEDLING SEED ORCHARDS OF Eucalyptus pellita IN INDONESIA - Budi Leksono (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2009)
The magnitude of the genotype-environment interaction (GEI) in seven six years old seedling seed orchards of Eucalyptus pellita established at three locations in Indonesia was examined by analyzing height and diameter. The seed orchard at each location consists of 121 families from three provenances of Papua New Guinea. The pooled sum of squares derived from analysis of variance of growth of the three provenances was used to estimate genetic parameters. These parameters were then used to calculate genetic gain as a result of both direct and indirect selections. The GEI across the three locations was very strong, while the results of pair-wise site analysis varied between the pairs of locations. The genetic correlations for pairs of locations were moderately high between South Sumatra and Riau;0.68 for dbh and 0.85 for height, but were lower between South Kalimantan and the other locations (0.32 to 0.56). The gains resulting from direct selection were apparently greater than those resulting from indirect selection. The genetic gains achieved in South Sumatra and Riau would decrease by 24% as a result of transfer to other sites, while transfer from South Kalimantan to Sumatra Island (and vice versa) would reduce in the genetic gain by 60%. Hence, the breeding population in South Kalimantan should be developed separately from those in South Sumatra and Riau